2009
DOI: 10.1159/000228980
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Internet Questionnaire for Risk Assessment in Preconception Care

Abstract: Aim: Validation of a self-administered Internet questionnaire for preconception risk assessment. Methods: Women with an appointment at the outpatient clinics for preconception care or fertility at the Erasmus Medical Center Rotterdam were requested to fill out the online questionnaire prior to attendance. Subsequently, the items of the questionnaire were verified by history taking during the first or next appointment. Agreement between the 2 screening methods (Internet vs. history taking) was calculated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 11 publications
(9 reference statements)
2
32
0
Order By: Relevance
“…None have been tested in UK primary care, but limited experience of using them, mainly from the USA and the Netherlands16 17 19 suggest their promise. These approaches have potential to increase women's knowledge and enable behaviour change, without inducing harm or anxiety 12 20 21.…”
Section: Introductionmentioning
confidence: 99%
“…None have been tested in UK primary care, but limited experience of using them, mainly from the USA and the Netherlands16 17 19 suggest their promise. These approaches have potential to increase women's knowledge and enable behaviour change, without inducing harm or anxiety 12 20 21.…”
Section: Introductionmentioning
confidence: 99%
“…Fourthly, concerning the validity of the reported risks, previous reports showed good to high agreement among most lifestyle-related, medical and obstetric history items obtained with Preparing For Pregnancy when compared to interviews [21]. An additional assessment by trained professionals seems necessary to verify women's answers with regard to their use of over-the-counter medication and their family history [20]. …”
Section: Discussionmentioning
confidence: 99%
“…The Erasmus University Medical Centre and the Dutch National Genetic Resource and Information Centre developed a free-access national web-site for individual pre-conception risk screening and information. Preparing For Pregnancy is a medically validated [20], freely accessible, web-based instrument for self-reporting by couples or to support systematic risk assessment by health care professionals. Preparing For Pregnancy is an updated and extended version of the previous Preconception Health Assessment form, a self-administered screening questionnaire validated in 2002 by de Weerd et al [21] and a pre-conception risk-assessment questionnaire used in the study ‘Parents to Be' [22].…”
Section: Methodsmentioning
confidence: 99%
“…Screening for women at dual risk for SEP/AEP may be feasible because most of the high-risk variables can be identified quickly using self-administered questionnaires that are highly reliable in addition to clinician history taking. 35 Surveys of women of childbearing age have demonstrated that the introduction of prepregnancy health promotion interventions would be welcomed and of potential benefit. 36 A recent major review of preconception interventions determined that there is some evidence that health promotion interventions are Not an effective contraception method S t test used Satterthwaite method to correct for unequal variances.…”
Section: Discussionmentioning
confidence: 99%